MANAJEMEN EMPOWERMENT EKONOMI PESANTREN MELALUI ENTREPRENEURSHIP : Case Study Pondok Pesantren Nurul Huda - Ayu Widia Lestari; Mustaqim Makki (AQaduna : Jurnal Hukum Ekonomi Syariah, 2023)
Economics in Islamic boarding schools has an important role in developing educational progress in terms of management, economics, entrepreneurs in order to be able to maintain and develop the pesantren economy, through the empowerment of the skills of students who are combined into a unit so as to uphold the skills in the pesantren. The formulation of the problem in the research is how to manage economic empowerment at the Nurul Huda Islamic Boarding School, and what factors are the obstacles and supporters in economic empowerment at the Nurul Huda Islamic Boarding School. This study uses a method whose data sources are obtained from direct sources in the field by means of interviews, observations, and documentation. Based on the results of this study, it can be concluded that Islamic boarding schools apply economic empowerment management through entrepreneurship which is managed by the students and formed in a management system, according to the needs and economic creativity that is applied in the pesantren environment. Conduct skill training for students in order to develop their potential in terms of economic creativity. Maximizing facilities, understanding the financial system, motivating to improve and create competitiveness in the future. Keywords: management, empowerment, economy, boarding school.